EVALUATION OF ATMOSPHERIC POLLUTION AS A COMPONENT OF LANDSCAPE-ECOLOGICAL PLANNING IN ENVIRONMENTAL MANAGEMENT OF KHARKIV REGION - МАКСИМЕНКО, Н. В.; ПЕРЕСАДЬКО, В. А.; ТІТЕНКО, Г. В.; КУЛИК, М. І. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
As part of the assessment phase of landscape-ecological planning (LEP) in Kharkiv region developed a cartographic model of ecological condition of air. Analyzed the total pollution caused by the activities of stationary sources, the groups of regions with different densities of total emissions into the atmosphere and found the reasons for such a situation. It was found that air emissions from stationary sources dominated sulfur dioxide, nitrogen dioxide, carbon monoxide and dust. On the basis of cartographic models created highlighted areas with critical levels of pollution, set trends in the temporal dynamics of pollution each of the substances in all areas of the field. The basic directions of environmental management for the region as a whole and proposed new method of presenting information on air pollution for this type of administrative units – the interpolation model, fully adapted to the needs LEP.